Optimizing Net Energy Efficiency of Vinyl Chloride Monomer (VCM) Production by Modifying Heat Transfer Process - Apriyani, Rizal; Alim, Rizky Putra Nur; Mustaqim, Rosid; Prasetya, Fauzi Sufyan (UPT Laboratorium Terpadu, Universitas Diponegoro, 2024)
The acetylene hydrochlorination process is a highly exothermic reaction, causing the reactor temperature to rise, which then requires cooling through a heat exchanger. A modification of the process is necessary to enhance the heat efficiency of the acetylene hydrochlorination by utilizing the heat generated by the reactor. Heat transfer fluid serves as a medium for both heating and cooling, enabling a looping heat transfer process. The heat transfer fluid system absorbs heat from the reactor and subsequently reuses this heat to warm the reactor feed, eliminating the need for additional energy input. The process modification was modeled using Aspen HYSYS, and the heat efficiency between the basic and modified processes was compared using the net-energy formula. The results showed that the net-energy (NE) for the basic and modified processes were 38,811,930.515 kJ/h and 18,702.951 kJ/h, respectively. This indicates that the modified process offers better energy efficiency, as the net-energy value is closer to zero compared to basic process. Thus, this modification improves the heat efficiency of VCM production through the acetylene hydrochlorination process. Copyright © 2024 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).